2020
DOI: 10.1021/acs.jpca.0c01943
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of Excited Electronic States in Nitrobenzene Measured by Ultrafast Transient Polarization Spectroscopy

Abstract: We investigate ultrafast dynamics of the lowest singlet excited electronic state in liquid nitrobenzene using Ultrafast Transient Polarization Spectroscopy (UTPS), extending the well known technique of Optical Kerr-Effect (OKE) spectroscopy to excited electronic states. The third-order non-linear response of the excited molecular ensemble is highly sensitive to details of excited state character and geometries and is measured using two femtosecond pulses following a third femtosecond pulse that populates the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…We note, however, that S 1 ( n 1 π 1 *) lifetimes of 5–6 ps reported in NB following direct excitation at wavelengths > 320 nm are far shorter than the τ 3 values we observe here when using a much higher energy 267 nm pump. , Given this observation, we therefore instead assign the τ 1 ≤ 30 fs DAS to a cascaded decay of the initially exited S 3 (π 1 π 1 *) and S 4 (π 2 π 1 *) states all of the way down to S 1 ( n 1 π 1 *), which then exhibits a lifetime described by τ 2 =160–190 fs. This extremely rapid sequential cascade through the singlet manifold (potentially including passage via the S 2 ( n 2 π 1 *) state) is consistent with the interpretation of earlier time-resolved photoelectron spectroscopy measurements made in NB using a 200 nm pump, as well as theoretical predictions. , An S 1 ( n 1 π 1 *) lifetime of 160–190 fs is also broadly consistent with recent transient polarization spectroscopy data obtained from pure samples of liquid NB using a multiphoton 780 nm pump …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We note, however, that S 1 ( n 1 π 1 *) lifetimes of 5–6 ps reported in NB following direct excitation at wavelengths > 320 nm are far shorter than the τ 3 values we observe here when using a much higher energy 267 nm pump. , Given this observation, we therefore instead assign the τ 1 ≤ 30 fs DAS to a cascaded decay of the initially exited S 3 (π 1 π 1 *) and S 4 (π 2 π 1 *) states all of the way down to S 1 ( n 1 π 1 *), which then exhibits a lifetime described by τ 2 =160–190 fs. This extremely rapid sequential cascade through the singlet manifold (potentially including passage via the S 2 ( n 2 π 1 *) state) is consistent with the interpretation of earlier time-resolved photoelectron spectroscopy measurements made in NB using a 200 nm pump, as well as theoretical predictions. , An S 1 ( n 1 π 1 *) lifetime of 160–190 fs is also broadly consistent with recent transient polarization spectroscopy data obtained from pure samples of liquid NB using a multiphoton 780 nm pump …”
Section: Discussionsupporting
confidence: 89%
“…Earlier work from the same group also noted some dependence on triplet state lifetime with both solvent and temperature, and supporting theoretical work indicated that bending of the nitro group out of the phenyl plane is a key reaction coordinate in driving efficient ISC . Much more recent measurements conducted on pure samples of liquid NB have reported S 1 ( n 1 π 1 *) lifetimes of just a few hundred femtoseconds . In the gas phase, Zewail and co-workers employed ultrafast electron diffraction to investigate the photochemical dynamics operating in NB following 267 nm excitation .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our work demonstrates that ultrafast electric field-resolved nonlinear spectroscopy can be a sensitive measure of electron dynamics. When applied to nonlinear spectroscopy of excited states [26,27], such as molecules and materials excited by attosecond pulses, electric field measurements can track the induced transient nonlinear polarization, which could offer new insight into ultrafast coherent electron dynamics.…”
Section: Discussionmentioning
confidence: 99%